PERBANDINGAN PENINGKATAN KEMAMPUAN PENALARAN MATEMATIS ANTARA PEMBELAJARAN BERBASIS MASALAH DAN PENEMUAN TERBIMBING DITINJAU DARI KEMAMPUAN AWAL MATEMATIS SISWA - Marfi Ario (JURNAL EKSAKTA PENDIDIKAN (JEP), 2017)
Mathematical reasoning ability is fundamental aspect in mathematic learning. Efforts to improve the ability of mathematical reasoning necessary. Based on that, this study was conducted to examine improvement of mathematical reasoning ability students who received problem based learning and guided discovery learning in terms of categories Early Mathematical Ability (EMA) students. This study was a quasi experimental research with the pretest-post-tes two treatment design. The population in this study were the students in class XI from one of SMK in Pekanbaru. Samples in this study were 76 students from two classes using purposive sampling technique. Instrument that used in this study was the questions of mathematical reasoning ability test. The findings of this study are: there is a difference in the improvement of mathematical reasoning ability among students who get problem based learning and students who gain guided discovery learning on medium KAM category students. In high and low KAM category students, there is no significant difference in the improvement of mathematical reasoning abilities between students who received problem based learning and students who received guided discovery learning.